c.2 - Galbraith, John Kenneth ("Cambridge, Mass", 1979)
This book had its origins almost two decades ago in India. In those years, the early sixties, the United States had a large and costly program of assistance to Indian agriculture. Its purpose was to help increase Indian food supplies and to lessen, however slightly, the poverty which is the fate of nearly all in India who make their living from the land.
Keywords: Poverty